We love Julie - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Julie mango in the Eastern Caribbean. A comprehensive manual A CARDI CTA co-publication, 2001. 94 pp. ISBN 976 617 009 6 CTA number 1073. 10 credit points Avalaible from Cardi for Carribean countries